Implementation of Phil-Iri Program and English Competence in Oral Read-ing of Grade 6 Pupils - Plotado, Uniqcca L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study explored the implementation of the Phil-IRI Program and its impact on the English oral reading competence of Grade 6 pupils in public elementary schools in San Marcelino, Zambales, Philippines. Using a descriptive-correlational approach with 557 pupils and 26 teachers in the district of San Marcelino, Zambales, it assessed oral reading competence levels before and after the program's implementation. Results showed that most pupils were at the instructional level pre-implementation but demonstrated significant improvements post-implementation. The findings highlight the value of regular reading assessments and interventions in addressing reading comprehension challenges. The study recommends ongoing evaluation of reading programs and professional development for teachers to enhance literacy outcomes and instructional effectiveness.